PERAN RETORIKA DALAM MEDIA SOSIAL DAN PENGARUHNYA TERHADAP PEMILIH MUDA PADA PEMILIHAN UMUM (Lembaga Studi Agama dan Masyarakat Aceh (LSAMA), 2023)
The strong role of social media in the world of politics is gaining attention which helps the younger generation to be politically literate, and increasing the participation of first-time voters is inevitable, so the role of rhetoric in social media and its influence on young voters in general elections is very important. This research uses descriptive qualitative methods, data collection is carried out by literature study, secondary data refers to data that has been collected and analyzed by other people. The research results show that the role of political campaigns on social media has a positive and significant effect on young voter behavior. The role of good political campaigns on social media can increase the behavior of young voters, the role of political campaigns on social media simultaneously (together) has a positive and significant influence on the behavior of young voters, and of course social media will play a very important role in influencing children's voting behavior. young. New voters will be interested in politics while relaxing, although there is the influence of social media through schools and families, but it does not have a significant effect because they are a generation that is familiar with media use.